2021
DOI: 10.3390/md19050277
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Anti-Inflammatory Effects of Sulfated Polysaccharides Isolated from the Edible Brown Seaweed, Sargassum fulvellum

Abstract: In the present study, the in vitro and in vivo anti-inflammatory effects of the sulfated polysaccharides isolated from Sargassum fulvellum (SFPS) were evaluated in lipopolysaccharide (LPS)-stimulated RAW 264.7 macrophages and zebrafish. The results indicated that SFPS improved the viability of LPS-stimulated RAW 264.7 macrophages from 80.02 to 86.80, 90.09, and 94.62% at the concentration of 25, 50, and 100 µg/mL, respectively. Also, SFPS remarkably and concentration-dependently decreased the production levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
3
12
0
Order By: Relevance
“…Hu et al (2014) associated the analgesic effect of fucoidan after intrathecal injection with inhibition of spinal astrocytic and microglial activation, proinflammatory mediator production, and mitogen-activated protein kinases (MAPK) activation. This hypothesis is supported by recent studies, which indicate suppression of the production of TNF-α, prostaglandins, and interleukins [13,14], as well as potent inhibition of kinases, including ENK, JNK, Akt [16], and MAPK p38 [12], by fucoidan. The rationality of topical application of formulations with fucoidan was confirmed in our recent study [47], in which fucoidan was found in the skin, plasma, and striated muscles.…”
Section: Anti-inflammatory Activitysupporting
confidence: 53%
See 1 more Smart Citation
“…Hu et al (2014) associated the analgesic effect of fucoidan after intrathecal injection with inhibition of spinal astrocytic and microglial activation, proinflammatory mediator production, and mitogen-activated protein kinases (MAPK) activation. This hypothesis is supported by recent studies, which indicate suppression of the production of TNF-α, prostaglandins, and interleukins [13,14], as well as potent inhibition of kinases, including ENK, JNK, Akt [16], and MAPK p38 [12], by fucoidan. The rationality of topical application of formulations with fucoidan was confirmed in our recent study [47], in which fucoidan was found in the skin, plasma, and striated muscles.…”
Section: Anti-inflammatory Activitysupporting
confidence: 53%
“…Due to the complexity of inflammation processes, there is an urgent need for the development of new and safe anti-inflammatory agents with multiple mechanisms of action. Anti-inflammatory mechanisms described for fucoidan include scavenging of free radicals [11,12], suppression of the production of nitric oxide, tumor necrosis factor-alpha (TNF-α), prostaglandin E2, interleukin-1 beta, and interleukin-6 [13,14], selective inhibition of cyclooxygenase-2 [12], and downregulation of the expression of mitogen-activated protein kinase p38, Akt, extracellular signal-regulated kinase (ENK), and c-Jun N-terminal kinase (JNK) [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, none of the fractions were able to stimulate the production of IL-10. These results agree with those found in the literature [ 50 , 51 ], where brown seaweeds also revealed anti-inflammatory potential. Han and co-workers [ 52 ] evaluated the anti-inflammatory effect of sargacromenol isolated from Sargassum horneri in RAW 264.7 macrophages stimulated by LPS.…”
Section: Discussionsupporting
confidence: 93%
“…A sulfated polysaccharide isolated from Sargassum fulvellum demonstrated a significant and concentration-dependent decrease in the production levels of NO, TNF-α, PGE2, IL-6, and IL-1β in LPS-treated RAW 264.7 macrophages [132].…”
Section: Cellular Signal/corticoresistancementioning
confidence: 94%